THE OPENNESS OF ACCESS AND BEHAVIOR OF DISPOSING OF GARBAGE ON THE RIVERBANKS - Ai Nurhayati; Guruh Burhanto (Lembaga Penelitian Universitas Pasundan, 2023)
The people of Loji village have limited access to the riverbanks which makes them a place to live rubbish. The purpose of this study is to show what kind of behavior and access the village community Loji behaved to throw garbage on the riverbank. The method used is interview and observation. The results of this study found that the open access factor makes people feel now the riverbanks have become common property and are used together to be used as a place of waste disposal. The concepts of access and rational choice are used because they can explain the behavior of residents to dispose of waste that pollutes and damages the environment.